2020
DOI: 10.1017/s0007114520000896
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the intestinal microbiota and the metabolites produced by the administration of ice cream and a dietary supplement containing the same probiotics

Abstract: The aim of the present work was to compare the capacity to modulate the intestinal microbiota and the production of metabolites after 14 d administration of a commercial dietary supplement and a manufactured ice cream, both containing the same quantity of inulin and the same viable counts of Lactobacillus acidophilus LA-5 and Bifidobacterium animalis BB-12, using the Simulator of the Human Intestinal Microbial Ecosystem (SHIME®) model. Samples of the colonic contents were evaluated microbiologically by real-ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 107 publications
(108 reference statements)
0
12
1
Order By: Relevance
“…The QseC sensor kinase role in intestinal microbiota composition was verified during the Shiga toxin producing O104:H4 E.coli infection. The C227–11 and C227–11 ::qseC strain were employed during in vitro infection of controlled colonic SHIME® model, to mimic the human gastrointestinal tract, evaluating the intestinal microbiota abundance through C227–11 infection [ 49 ], as detailed illustrated (Fig. 1 a and b).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The QseC sensor kinase role in intestinal microbiota composition was verified during the Shiga toxin producing O104:H4 E.coli infection. The C227–11 and C227–11 ::qseC strain were employed during in vitro infection of controlled colonic SHIME® model, to mimic the human gastrointestinal tract, evaluating the intestinal microbiota abundance through C227–11 infection [ 49 ], as detailed illustrated (Fig. 1 a and b).…”
Section: Resultsmentioning
confidence: 99%
“…The reactor was adapted for this study, where the transverse and descending colon were replaced by the triplicate of the ascending colon (pH 5.6–5.9), aiming to obtain replicates of the experiment for statistical comparison of the data (Fig. 1 a), with experimental settings as previously described [ 49 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A study, recently published by our group, using the Simulator of the Human Intestinal Microbial Ecosystem (SHIME®) showed that synbiotic ice cream produced with Bifidobacterium animalis subsp. lactis BB-12 and Lactobacillus acidophilus LA-5 and inulin favoured the maintenance and metabolic activity of probiotics added, due to the increase in the proportion of SCFA (acetate, propionate and butyrate) (19) .…”
mentioning
confidence: 99%